Production, characteristics and use of magnetic biochar nanocomposites as sorbents. (May 2023) - Burbano, A.A.; Gascó, G.; Horst, F.; Lassalle, V.; Méndez, A.
Abstract: Magnetic biochar nanocomposites were obtained by in-situ co-precipitation of magnetite nanoparticles into carbon-based matrixes prepared by three different procedures: i) pyrolysis of sunflower husk (MBCSFH ); ii) hydrothermal carbonization (HTC) of sunflower husk (MHCSFH ) and iii) HTC of orange juice residue (MHCOR ). Besides, two magnetic carbon nanocomposites were obtained in the same way using commercial activated carbon (MAC) and charcoal (MCC). All the materials were widely characterized by elemental analysis, N2 isotherms, FTIR, and Z potential and used in the sorption of malachite green (MG) from water. Kinetic fitting was done using pseudo-first-order and pseudo-second-order kinetic models, where it was found that experimental data fitted well with the second-order kinetic model. MHCSFH and MHCOR exhibited the maximum removal efficiencies (77.00% and 82.18%) compared to their corresponding carbon precursors (63.32% and 34.29%). The post-sorption characterization of MHCOR indicates electrostatic interactions, electron sharing, and п-п interactions and pore filling are the principal interactions between sorbent and MG. In addition to the synthesis and characterization of magnetic biochar nanocomposites, this research demonstrated the capacity of sorbents materials for pollutants removal. Graphical abstract: Image 1 Highlights: Magnetic carbon sorbents were prepared by magnetite nanoparticles co-precipitation. Carbon precursors were prepared by pyrolysis and hydrothermal carbonization. Magnetic carbon nanocomposites were used for malachite green removal. Magnetite nanoparticles enhance malachite green sorption of carbon precursors.